The influence of public relations on luxury brand marketing through female fashion magazines - LI, Yiru (2010)
Female fashion magazine is one of the most important Public relations (PR) partners for luxury fashion company, PR plays an important role in marketing. This study uses editorial pages of female fashion magazine as object to discover the influences from PR activities on luxury fashion marketing.